2018
DOI: 10.1021/acs.macromol.8b01014
|View full text |Cite
|
Sign up to set email alerts
|

Semi-bald Micelles and Corresponding Percolated Micelle Networks of Thermogels

Abstract: As an injectable and biodegradable hydrogel, thermogels of amphiphilic block copolymers of polyester and polyether in water show great potential in biomedical fields. It is challenging to reveal the mechanism behind the reversed thermogelling with sol−gel transition upon heating. Herein, a computer simulation and corresponding experiments are combined to examine aqueous systems of amphiphilic diblock copolymer of methoxypoly(ethylene glycol) and poly(D,L-lactideco-glycolide). We synthesized the copolymer via r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 68 publications
4
96
0
Order By: Relevance
“…7C). 45 Unlike these linear block-copolymer amphiphiles however, our branched multi-block polyurethanes contain a greater proportion of hydrophilic PEG groups over hydrophobic PPG and PCL groups randomly-distributed throughout the polymer structure, including along their branches. The complexity of the polymer structures studied herein result in unique micelle aggregation mechanism distinct from the aforementioned three, and may contain a combination of features from Pluronic-like and 'micelle-bridging' mechanisms.…”
Section: Effects Of Polymer Branches On Thermogel Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…7C). 45 Unlike these linear block-copolymer amphiphiles however, our branched multi-block polyurethanes contain a greater proportion of hydrophilic PEG groups over hydrophobic PPG and PCL groups randomly-distributed throughout the polymer structure, including along their branches. The complexity of the polymer structures studied herein result in unique micelle aggregation mechanism distinct from the aforementioned three, and may contain a combination of features from Pluronic-like and 'micelle-bridging' mechanisms.…”
Section: Effects Of Polymer Branches On Thermogel Propertiesmentioning
confidence: 99%
“…These polymers can form thermogels by hierarchical self-assembly triggered by warming: dehydration of the hydrophobic polymer segments rst brings about micelle formation due to hydrophobic interactions, which in turn then further self-assemble to form a non-covalently crosslinked network of micelles that entraps water to form stable gels. [41][42][43] The exact mechanism of the thermogel formation from micelle self-assembly depends on the structure and composition of the amphiphilic block-copolymer backbone, with micelle aggregation, jamming and bridging 42,44,45 all shown to be plausible.…”
Section: Introductionmentioning
confidence: 99%
“…Along with SANS, 3D-DLS is also a powerful method to analyze concentrated solutions or turbid systems with multiple scattering as compared to conventional DLS, which can be applied to samples with single scattering. In reports by Cui et al [25], the thermoresponsive gelation behavior of PEG-PLGA solution was characterized by 3D DLS. They confirmed the existence of larger and highly irregular clusters for the concentrated system (25 wt%) as compared to the low-concentration solution (1 wt%) In their report, a connected micellar structure in thermoresponsive hydrogels was also detected by fluorescence resonance energy transfer (FRET).…”
Section: Structural Analysis Of Hydrogels Composed Of Block Copolymermentioning
confidence: 99%
“…It was revealed that small spherical micelles were observed at concentrations of 5 wt% and 10 wt%, and these micelles united into a larger one, with the concentration increasing up to 20%, and a columnar structure was formed at concentrations of 25 wt% and 30 wt% ( Figure 2). Monte Carlo simulation was also carried out by Cui et al [25] in order to reveal the mechanism behind reversed thermoresponsive gelation with sol-gel transition upon heating. In their system, with a new type of micelle, the semi-bald micelle, as precursor for thermoresponsive gelation, they demonstrated that the structure of thermoresponsive hydrogels was a percolated micelle network with hydrophobic channels that evolved from semi-bald micelles ( Figure 3).…”
Section: Structural Analysis Of Hydrogels Composed Of Block Copolymermentioning
confidence: 99%
“…The layered scaffold fabricated with only one raw biomaterial is relatively less reported, and the corresponding investigation of such a simple scaffold system has its own right. Poly(lactide- co -glycolide) (PLGA) is a very useful biodegradable polymer owing to its tunable biodegradation rate, very good mechanical and processing properties, and so on [15], [16], [17]. PLGA was previously used to fabricate the integrated bilayered scaffolds by adjusting the different pore sizes or different porosities in the chondral and osseous layers.…”
Section: Introductionmentioning
confidence: 99%